Raum. Macht. Inklusion Inklusive Räume erforschen und entwickeln - Hoffmann, Mirjam; Hoffmann, Thomas; Pfahl, Lisa; Rasell, Michael; Richter, Hendrik; Seebo, Rouven; Sonntag, Miriam; Wagner, Josefine (Verlag Julius Klinkhardt, 2023)
The volume "Space. Power. Inklusion." brings together selected papers from the 35th Annual Conference of Inclusion Researchers (IFO), which was hosted by the University of Innsbruck in cooperation with KPH Edith Stein from February 23-25, 2022. Under the impression of the global crises intensifying due to the COVID-19 pandemic, the conference focused on the importance of social spaces and powerful social orders for inclusion research. In this context, exclusion can be understood as the expropriation of spaces and their hegemonic occupation; inclusion, on the other hand, as their appropriation, radical democratization, and liberation. The contributions show how exclusive or inclusive spaces can be theoretically conceived, empirically investigated, and practically developed in current research projects.